Effects of Different Storage Media, Temperature, and Time on Osteoblast Preservation in Autogenous Bone Grafts: A Histomorphometrical Analysis - Hamidreza Arabiun; Hossein Bordbar; Seifollah Dehghani Nazhvani; Reyhaneh Ebrahimi; Ehsan Aliabadi; Ilnaz Ghanbari (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Autogenous bone graft is the gold standard for bone reconstruction. Osteogenic cells must be kept viable in graft for a successful procedure. In extracorporeal preservation of grafts during surgery, three different factors may influence the quality of grafts. These factors include temperature, storage medium, and time interval. Purpose: In this study, we evaluated the effects of different storage media, temperatures, and times on osteoblast count in autogenous bone grafts, preserved extracorporeally. Materials and Method: Samples were obtained from iliac crest region in a goat. The grafts were preserved in 36 groups of different storage time, temperature, and medium. Samples were histomorphometrically analyzed to determine osteoblast count as the criteria of graft quality. Results: In almost all samples, room temperature was the most and incubator was the least favorable storage temperatures. In grafts preserved in room temperature, no difference was noted between normal saline and Ringer's lactate solution and in almost all of the samples autologous blood and dry environment were more favorable media than Ringer's lactate solution. The effect of storage time was highly depended on the combination of temperature and solution. Conclusion: The results demonstrated that for preserving as many osteoblasts as possible in bone grafts, the best temperature was room temperature and the least favorable temperature was incubator. In addition, when bone fragments were preserved in room temperature, the best medium for graft storage was blood, which showed better results than normal saline and Ringer's lactate solution.